Non-isothermal decomposition of biomolecules studied by means of temperature-programmed desorption mass spectrometry - Pokrovskiy, V. A.; Galagan, N. P.; Kulik, T. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2001)
Temperature-programmed desorption mass spectrometry (TPD MS) is discussed with reference to studies of modified pyrogenic oxides. Simple theoretical models are presented in order to allow an approximate analytical treatment of TPD MS data. Rate constants for first- second- and third-order reactions have been obtained. Products of thermal decomposition of carbonized surface layer has been observed and identified. The different pathways of uni- and bimolecular desorption were investigated and rate constants of reactions has been derived from TPD MS measurements. Adsorption and thermal stability of several polyketides has been studied by TPD MS in condensed and adsorbed states. Mass spectrometric analysis allowed observing correlation between chemical structure of morine and venorutone molecules and mechanism of thermolysis. Decomposition of carbon carcass of chromone, the bensanelled y-pyrone in particular, resulted in formation of fragments with mass numbers 91, 95, 108, 111 m/z. Decomposition occurred in three stages with maxima at 200, 280, 380°C for morine and 240, 320, 450°C for venorutone. Presence of carbohydrate residue (ramnose, glucose) in venorutone molecule caused two additional stages of thermolysis in comparison with morine, maxima being located at 220 and 280°C. In this case, different to previous one, the substituted y-pyrone has been produced being characterized by mass numbers 72, 97, 102, 126 m/z. Comparison of adsorption parameters for venorutone and carbohydrates has shown that carbohydrate residue played main role in adsorption of venorutone molecules on ultrafine silica surface. The ring C of venorutone molecule stayed free in adsorption process which attested the fact that hydroxyl group in position 4' responsible for biological activity of flavonoids, did not participate in adsorption. It allows the ring C preserve its antioxidant, membrane- and capillary-stabilizing activity in bound state.